PENGARUH GAYA KEPEMIMPINAN DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA LATTERIA GELATO JAKRTA BARAT - Misel Amelia Putri; Nurdinni Tilova (Al Hasanah Barokah Foundation, 2026)
This study aims to analyze the influence of Leadership Style and Teamwork on Employee Performance at Latteria Gelato, both partially and simultaneously. The research uses a descriptive quantitative method with 46 respondents selected through purposive sampling. The results of the regression analysis show that Leadership Style partially has a significant effect on Employee Performance, as indicated by the regression equation Y = 4.132 + 0.478 X1 and an R Square value of 0.612 (61.2% of the variation is explained by Leadership Style). The partial t-test for Leadership Style shows a t-count of 5.736 > t-table of 2.017 and a significance value of 0.000 < 0.05, so H₀ is rejected and Hₐ is accepted. Likewise, Teamwork also has a significant partial effect on Employee Performance, with the regression equation Y = 3.892 + 0.529 X2 and an R Square value of 0.645. The t-count for Teamwork is 6.104 > t-table and the significance value is 0.000 < 0.05, indicating H₀ is rejected and Hₐ is accepted. Simultaneously, Leadership Style and Teamwork significantly influence Employee Performance, as shown by the regression equation Y = 2.987 + 0.311 X1 + 0.402 X2 and an R Square value of 0.721. The F-test yields an F-count of 54.789 > F-table of 3.21 with a significance value of 0.000 < 0.05, confirming that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that both Leadership Style and Teamwork simultaneously have a significant effect on Employee Performance at Latteria Gelato.